Organização de uma disciplina na modalidade a distância na perspectiva da Atividade Orientadora de Ensino abordando tecnologias digitais no ensino de Matemática - Gonçalves, Elivelton Henrique (2023)
This research aimed to analyze the methodological organization and development of an undergraduate subject in the distance education modality based on the theoretical-methodological principles of the Teaching Guiding Activity addressing the use of digital technologies in Mathematics teaching. The investigation was based on the Historical-Cultural Theory, specifically on the Teaching Guiding Activity, grounded in the historical-dialectical materialist method. The empirical material was produced in 2020 and 2021, involving the participation of eight undergraduate students in Mathematics, and comprised the use of online questionnaires, the organization, and development of the teaching of the subject “Information and Communication Technologies in Mathematics Education” offered in the second group of the undergraduate course in Mathematics by distance modality at the Federal University of Uberlândia. For analysis, we structured the empirical information into two isolates, consisting of episodes and scenes, in which we discuss: the methodological organization of the discipline based on the formative needs of the undergraduate students in Mathematics; and the process, materialized in the offer of the subject, of developing this organization and the approach to the use of digital technologies in Mathematics teaching from the perspective of the undergraduates. The research results in the need for the teacher trainer/author to constantly and intentionally organize, monitor, and evaluate their teaching activity; know the characteristics and material conditions of distance education, the audience, and their formative needs; develop a dialogical, detailed and structured didactic material; prioritize the use of synchronous and asynchronous tools and strategies that allow for dialogue, interaction and sharing among those involved, intensifying their presence in the conduct of these processes; and develop an achievable and flexible schedule. Regarding the approach to the use of digital technologies in Mathematics teaching, the results indicate that promoting experiences and productions of teaching situations in which such technologies integrate with the study of mathematical content, constitutes a mobilizer of understandings regarding the use of digital technologies to teach and learn Mathematics. However, the investigation shows that the central point of highlight regarding the proposed and conducted methodological organization and development is the fact that they promoted human interactions and approximations in the processes of distance education materialized throughout the classes, which, at least in this research, reveals itself as one of the main contributions provided by the Teaching Guiding Activity to this educational mode. Thus, this research points in two directions: first, it emphasizes that distance education demands intentional organization and conduct, systematic monitoring, and promotion of synchronous and asynchronous human interactions, taking into account its specificities and the audience served, and not mere adaptations without any theoretical-methodological organization; and second, it emphasizes the need, when proposing the approach to the use of digital technologies in Mathematics teaching in a subject, that there is, exactly, the study, problematization, and integration of the use of digital technologies in Mathematics teaching during the teaching of the subject.